Evaluation Of Ph Quality And Water Capacity Of Yogurt Of Etawa Goat Milk (Capra Aegagrus Hircus) With The Addition Of Mangga Golek Fruit Juice - Liston; J.M.Sihombing; K.M.Berutu (Jurnal Peternakan Integratif, 2023)
Milk is the product of livestock in the form of white liquid contains nutrients that are very good for humans. This study aims to determine the quality of pH (Hydrogen Potential) and moisture content of Peranakan Etawa (PE) goat milk yogurt with the addition of golek mango juice at different levels. The research was conducted at the Laboratory of the Faculty of Agriculture and Animal Husbandry, Tjut Nyak Dhien University. The research method used a completely randomized design (CRD) with 4 treatments and 5 replications, namely P0, P1, P2 and P3 by testing the pH and moisture content of yogurt.The results showed that the addition of golek mango juice to yogurt gave the same effect on yogurt pH and water content. The optimal pH value, water content and dry matter of etawa peranakan goat milk yogurt in treatment P0 without the addition of golek mango juice with an average pH value of 3.98, water content of 84.4% and dry matter of yogurt of 15.6%. Yogurt dry matter is better in the P0 treatment